Stress fracture in the world class athlete: a case study - Jensen, J. E. (Medicine & Science in Sports & Exercise, 1998)
The use of a specifically programmed, pulsed, low-intensity ultrasound device to shorten the time of healing was investigated in a well-known gymnast with an Olympic deadline. Stress fracture presents a difficult problem in the high performance, world-class athlete. Competitive demands provide little tolerance for, or agreement with, prolonged periods of rest which are the first line of conservative treatment methods. The use of a specifically programmed, pulsed, low-intensity ultrasound device to shorten the time of healing was investigated in a well-known gymnast with an Olympic deadline. Prior animal, in vitro, and clinical studies had established the safety and effectiveness of this device in fractures. The location of the stress injury was in the mid-tibia which is considered to present the greatest challenge to an early healing result. The low-intensity ultrasound device was prescribed for daily use at home. At 3 wk after the start of low-intensity ultrasound, the stress fracture responded well and the patient was allowed use of tumble track, trampoline, and to do some weight-bearing activities, such as jumping in the pool and loading-type activities. At 4.5 wk, the patient progressed to full workout activities and participated in a trial meet for the Olympics. At 6 wk, the patient's participation in the women's gymnastic team event was a factor in the United States receiving a gold medal.